The Simple Economics of Benefit Transfers - Snower, Dennis (Washington, D.C. : International Monetary Fund, 1995)
The paper examines the employment and unemployment implications of permitting unemployed people to use part of their unemployment benefits to provide employment vouchers to the firms that hire them. This opportunity to transfer unemployment benefits into employment subsidies--'benefit transfers' for short--would help replace the unemployment trap by an incentive to work. The vouchers rise with people's unemployment durations and with the amount of training provided. The policy would be costless to the government since the cost of the employment vouchers is set equal to the amount saved on unemployment benefits. It would not be inflationary since the long-term unemployed, on whom the vouchers are targeted, have little influence on wage setting.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet